Suspected X-linked facial dysmorphia and growth retardation in related Labrador retriever puppies. (February 2017) - Dierks, C.; Hoffmann, H.; Heinrich, F.; Hellige, M.; Hewicker-Trautwein, M.; Distl, O.
Highlights: A previously unreported syndrome of congenital malformations is reported in seven Labrador retriever puppies. Affected puppies exhibit a brachycephalic-like face and skull, along with growth retardation. The condition is not compatible with survival of affected puppies. On the basis of pedigree analysis, an X-linked pattern of inheritance is suspected. Abstract: Seven male Labrador retriever puppies from four different litters were identified with a brachycephalic-like face and skull, associated with low birth weight, severe growth retardation, and reduced abilities to crawl and suckle, which were not compatible with survival. Excessive doming of the cranium, brachygnathia superior and inferior, and an abnormally opened fontanelle were found in all affected puppies by computed tomography and at post-mortem examination. Pedigree analysis supported an X-linked recessive mode of inheritance.